Design possibilities for the e-Schoolbag: addressing the 1:1 challenge within China - Gu, Xiaoqing; Xu, Xiaojuan; Wang, Huawen; Crook, Charles (Wiley, 2016)
There is widespread enthusiasm for 1:1 computing in education. Recognizing that secure innovation of educational practice should be built upon contextual sensitivity, this article reported two case studies anticipating the potential development of 1:1 classes in the particular cultural context of China. The first case described how the new technology of e-Textbooks could align with a tradition where the textbook is central to teaching practice. A science teacher used the e-Textbook to design his pedagogy to accommodate the contextual learning needs of the classroom. Students reported a positive reaction. They understood that new learning possibilities were crafted through this engagement with diversified media formats that content fitted their class, and this gave them increased confidence in relation to both student–computer and interpersonal interaction. The second case study described how a social app could align with the local tradition of practice whereby a student’s performance in front of class is an important part of instructional practice. In this case, students who were learning native Chinese were offered the opportunity for performing within a novel “digital stage”: revealing high levels of engagement and a strengthening confidence with language performance.